Impact of Trilingual Efficiency on the Working Memory and Inhibitory Control in Undergraduates: A Case Study of Pakistan - Muhammad Saram Khalid; Sharif, Humera; Habib, Asad; Nayyer Hassan (Forum for Linguistic Studies, 2024)
In recent years, the phenomenon of multilingualism has spread throughout the world. Pakistan offers an intriguing picture of multilingualism, yet little research has been done in this domain. The previous body of research in the multilingualism and cognition domain had produced inconsistent findings. This study aimed to investigate the positive impact of multilingualism on executive functions of inhibitory control and working memory in undergraduate students. Twenty participants were hired from a call center organization. A language history questionnaire (LHQ3) was administered along with the Simon and Corsi experimental tasks to measure inhibition and working memory. A simple linear regression analysis was run to find the impact of multilingualism. The data findings showed no impact of multilingualism on inhibitory control and working memory. The results showed insufficient statistical evidence to prove the multilingual advantage. Moreover, the results also projected the involvement of multiple confounding variables that may be the principal reason for inconsistent findings in this field of research. Hence, the bilingual advantage hypothesis is rejected because the findings could not predict the generalizability of the positive effect of multilingualism on the executive functions in the larger population of undergraduates. The study suggests that a multiple hierarchical regression model may be more productive, including multiple confounding variables.